Dielectric polymer composites with ultra-high thermal conductivity and low dielectric loss. (20th October 2022) - Yu, Xiangyan; Bhatti, Muhammad Rehan; Ren, Xintong; Steiner, Pietro; Di Sacco, Federico; Dong, Ming; Zhang, Han; Papageorgiou, Dimitrios; Portale, Giuseppe; Kocabas, Coskun; Bastiaansen, Cees W.M.; Reece, Mike; et al.
Abstract: Polymer based dielectric materials with simultaneously high thermal conductivity and low dielectric loss are highly desirable in various applications like energy storage, thermal management and electronic packaging. Polymer dielectrics generally benefit from good electrical insulation, high breakdown strength, high toughness and low density but suffer from very low thermal conductivity (0.1–0.5 W m −1 K −1 ). Herein we propose a new strategy to overcome this compromise; solid-state drawing of ultra-high molecular weight polyethylene (UHMWPE) films doped with a small amount of nanodiamonds (NDs). The resulting orientation of UHMWPE macromolecules and the nanofiller significantly improves the thermal conductivity along the stretching direction, while the dodecane surface functionalization of the NDs endows a robust interface between the matrix and filler, which minimizes the thermal resistance and dielectric loss. Our composites film (2 wt% NDs) shows an ultra-high thermal conductivity of 60 W m −1 K −1 in the drawing direction and very low dielectric loss, both at low and high electric field. More generally, herein we demonstrates that the interfaces introduced by the nanofillers do not necessarily cause an increase in dielectric loss at high electric field and a decrease in thermal conductivity, providing a new direction for the design of novel polymer based dielectric and functional materials. Graphical abstract: Image 1